2009
DOI: 10.1039/b820659g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of pentavalent uranyl complexes. The remarkable stability of UO2X (X = I, SO3CF3) in non-aqueous solutions

Abstract: The reaction of [UO(2)I(2)(THF)3] with KC(5)R(5) (R = H, Me) or K(2)C(8)H(8) in pyridine gave crystals of [{UO(2)(py)(5)}{KI2(py)2}]. (1), which were desolvated under vacuum into pulverulent [UO(2)(py)2.2KI2] (2).Similar reactions with [UO2(OTf)2] afforded [UO2(py)2.3K(OTf)2] (3) as a powder and crystals of [{UO(2)(py)(5)}2{K(3)(OTf)(5)}. py]. (4.py), which were also obtained together with crystals of [{UO2(py)5}2{K(OTf)2(py)2}][OTf] py (5. py) by treating [UO2(OTf)2] with KC(4)Me(4)P. Crystals of 6. py, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 103 publications
3
76
0
1
Order By: Relevance
“…Crystals of all complexes apart from 2-Gd were grown from pyridine solutions at either room temperature or −30°C and were found to be suitable for single crystal X-ray diffraction studies; selected bond lengths and angles for 2-Ln are detailed in Table 1. (11) 172.73 (16) The general synthetic procedure was also successful in THF solvent to afford the analogous THF adducts [{UO 2 Ln-(THF) 2 (L)} 2 ] 2THF-Ln (Ln = Ce, Sm, Dy, Yb). These complexes were prepared on a small scale in NMR tubes, although 2THF-Sm and 2THF-Dy were also prepared and isolated from bulk-scale reactions as pink-red (28% yield) or pale brown (16%) powders, respectively; the THF adducts are as poorly soluble in common organic solvents as the pyridine adducts.…”
Section: Synthesis Of the Dimericmentioning
confidence: 98%
“…Crystals of all complexes apart from 2-Gd were grown from pyridine solutions at either room temperature or −30°C and were found to be suitable for single crystal X-ray diffraction studies; selected bond lengths and angles for 2-Ln are detailed in Table 1. (11) 172.73 (16) The general synthetic procedure was also successful in THF solvent to afford the analogous THF adducts [{UO 2 Ln-(THF) 2 (L)} 2 ] 2THF-Ln (Ln = Ce, Sm, Dy, Yb). These complexes were prepared on a small scale in NMR tubes, although 2THF-Sm and 2THF-Dy were also prepared and isolated from bulk-scale reactions as pink-red (28% yield) or pale brown (16%) powders, respectively; the THF adducts are as poorly soluble in common organic solvents as the pyridine adducts.…”
Section: Synthesis Of the Dimericmentioning
confidence: 98%
“…[9] It is now clear that many initial synthetic attempts resulted only in uranyl reduction, and not in alkylation. [10] For example, Ephritikhine and co-workers demonstrated that reaction of one equivalent of Li(CH 2 SiMe 3 ) with [UO 2 I 2 (THF) 3 ] or [UO 2 (OTf) 2 ] in pyridine resulted in the formation of a uranyl(V) complex, [11] while Seyam observed formation of UO 2 and biphenyl upon reaction of UO 2 Cl 2 with two equivalents of phenyllithium. [12] Only recently have chemists developed strategies for inhibiting the reduction of uranyl.…”
mentioning
confidence: 98%
“…[1,2] For example, new routes to the singly reduced, pentavalent uranyl have been developed and have facilitated fascinating new Lewis acidbase interactions between the oxo groups and alkali metals, [3,4] boranes, [5][6][7] transition metals, [8] rare earth metals, [9] and other uranyl cations. [10] In some cases it is evident that oxo group functionalization can modify the U VI / U V reduction potential such that reduction is facilitated.…”
mentioning
confidence: 99%